Empirical Investigation on Compressive Strength of Geopolymer and Conventional Concretes by Nondestructive Method - B. Ravali; K. Bala Gopi Krishna; D. Ravi Kanth; K. J. Brahma Chari; S. Venkatesa Prabhu; R. Ramesh (Advances in Materials Science and Engineering)
Need of construction is increasing due to increase in population growth rate. The geopolymer concrete is eco-friendly than ordinary concrete. Current experimental investigation was conducted on ordinary and geopolymer concrete using nondestructive testing (NDT) tests like ultrasonic pulse velocity (UPV) test and rebound hammer (RH) test. Cube specimens of dimensions 150 mm × 150 mm × 150 mm are used to conduct these tests at 7, 14, and 28 days. Proportions considered for concrete are cement-fly ash-river sand (100-0-100% and 60-40-100%), cement-fly ash-robo sand (100-0-100% and 60-40-100%) whereas geopolymer concrete fly ash-metakaolin is taken in proportions of 100-0%, 60-40%, and 50-50%. Alkaline activators (sodium hydroxide and sodium silicate with molarity 12M) were used in preparing geopolymer concrete. The major objective of the current study is to obtain relation between compressive strength of concrete and UPV values.